Sejarah Falak Nusantara Melayu - Nor Azam bin Mat Noor (Al-Marshad: Jurnal Astronomi Islam dan Ilmu-Ilmu Berkaitan, 2020)
Malay archipelago is considered as a major Islamic development which includes the Malay archipelago stretching from Sumatra in the west to Sulawesi in the east. Arab traders with the help of the monsoon wind picked up many stops to trade and develop Islam at the same time. Thus Falak is a fardhu kifayah who needs to be taught to strengthen the obligatory practices of 'obligatory' in Islam such as performing prayers, facing the Qiblah, fasting and performing zakat. Arab traders also married local women and settled mostly kept in the Malay region while the next generation of pervasive importance of astronomy through Saiyid faction and Sheikh which have a high reputation among the society.